Decreased CX3CL1 Levels in the Cerebrospinal Fluid of Patients With Alzheimer’s Disease - Perea, Juan R.; Lleó, Alberto; Alcolea, Daniel; Fortea, Juan; Ávila, Jesús; Bolós, Marta (Frontiers in Neuroscience, 2018)
Alzheimer´s disease (AD) is a neurodegenerative disease characterized by the presence of neurofibrillary tangles, constituted by tau protein, and plaques formed by amyloid-beta protein. The disease courses with high neural damage, which leads to memory loss and death. Here we analyzed the presence of CX3CL1, a chemokine expressed by neurons, in cerebrospinal fluid (CSF) samples from control subjects and patients with mild cognitive impairment (MCI) and AD dementia. CX3CL1 was decreased in the CSF of AD dementia patients compared to control subjects. However, there was not difference in plasma samples from the same subjects.